SELECTED LEAST SIGNIFICANT BIT APPROACH FOR HIDING INFORMATION INSIDE COLOR IMAGE STEGANOGRAPHY BY USING MAGIC SQUARE - Sahar Mahdie Klim (Journal of Engineering and Sustainable Development, 2017)
The main goal of steganography is to hide the existence of any secret data from the eye of third party, so the resultant stego-image must appear normal and not suspicious after the impeding process. Stego-image must have an acceptable quality in comparison with its size. Moreover, its size has to be on the rate of the usual Internet images, because it is required to be sent by this medium. This work focuses on these problems, using a novel Selected Least Significant Bit method. Standard color images were used to hide the data. The proposed approach has been evaluated and the results had been analyzed. The obtained results showed clear enhancements on the impeding space considering previous related works.